2002
DOI: 10.1042/bst0300441
|View full text |Cite
|
Sign up to set email alerts
|

Additional signals from VPAC/PAC family receptors

Abstract: The receptors for the neuropeptides vasoactive intestinal polypeptide and pituitary adenylate cyclase-activating polypeptide are strong activators of adenylate cyclase, but recent evidence suggests that they can elicit a number of additional intracellular signals. Some of these are likely to be downstream of the conventional adenylate cyclase pathway, but it is now clear that others reflect novel primary coupling events of the receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Within the group II secretin receptor G protein-coupled receptor family, the VPAC 1 and VPAC 2 receptors have been identified, cloned (Harmar et al, 1998) and are considered to be the main physiological receptors that mediate the effects of VIP. Members of this family couple to the production of cAMP, and are capable of activating additional signalling pathways (McCulloch et al, 2002). Both VPAC 1 and VPAC 2 receptors have been shown to be expressed in equal amounts in human cerebral arteries regardless of endothelium; however, their location remains undetermined (Knutsson and Edvinsson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Within the group II secretin receptor G protein-coupled receptor family, the VPAC 1 and VPAC 2 receptors have been identified, cloned (Harmar et al, 1998) and are considered to be the main physiological receptors that mediate the effects of VIP. Members of this family couple to the production of cAMP, and are capable of activating additional signalling pathways (McCulloch et al, 2002). Both VPAC 1 and VPAC 2 receptors have been shown to be expressed in equal amounts in human cerebral arteries regardless of endothelium; however, their location remains undetermined (Knutsson and Edvinsson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The pituitary adenylate cyclase activating peptide (PACAP) receptor is best known for its ability to stimulate adenylate cyclases, cAMP production, and PKA (Ohtaki et al, 1993;McCulloch et al, 2002) but also signals through G q/11 to phospholipase C (PLC) (Spengler et al, 1993;McCulloch et al, 2002). PACAP1 receptors (PAC 1 Rs), specific for PACAP, are expressed predominantly in the brain, whereas VPAC receptors, which bind both VIP and PACAP, are more common in the periphery (Hashimoto et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…First, VIP neurons in the SCN directly innervate GnRH neurons in the rostral preoptic nucleus (rMPN) (van der Beek et al, 1997;Horvath et al, 1998). Second, GnRH neurons express the VIP/ PACAP receptor subtype 2 (VPAC 2 ) receptor subtype (Smith et al, 2000), which is coupled to the stimulatory G-protein (Gs) signal transduction pathway that leads to an accumulation of cAMP (McCulloch et al, 2002). Interestingly, Chappell et al (2000) reported that cAMP levels in the anteroventral periven-tricular nucleus (AVPV) exhibit a diurnal rhythm that is markedly analogous to the rhythm of VIP.…”
Section: Introductionmentioning
confidence: 99%